Guided Wave Energy Transfer in Composite Sandwich Structures and Application to Defect Detection - Siavash Shoja; Viktor Berbyuk; Anders Boström (Shock and Vibration)
In this study, energy transmission of the guided waves propagating in composite sandwich structures is investigated in a wide range of frequencies using numerical simulations. The effects of different potential defects on the guided wave energy transmission are explored in such structures. Furthermore, the accuracy of homogenization methods for finite element modelling of guided wave propagation in sandwich structures is studied with the aim of reducing the computational burden of the simulations in the low range of frequencies. A 2D finite element model is developed and verified by comparing the results with the dispersion curves. In order to examine homogenization methods, the homogenized stiffness matrices of the sandwich material and the laminate skin are calculated using classical laminate theory. Results show that core-skin debonding causes absence of wave energy leakage from the skin to the core material in that region in a specific range of frequencies. The results are also obtained for the delamination within the skin and compared with the healthy material. Finally, for the guided waves in the low range of frequencies, it is possible to use the homogenization methods to create the finite element models and reduce the solution time.